Media ABC Lima Dasar dalam Meningkatkan Adab pada Anak TPA Musholla Al Iman - Istijabath Istijabath; Vera Imanti; Galih Fajar Fadillah (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2025)
The formation of manners from an early age is crucial in building children's character with noble morals. Children at the Al-Quran Educational Park (TPA) often face challenges in understanding and applying adab values ​​in everyday life. This service activity aims to implement the Five Basic ABC Media as an intervention effort to increase understanding and application of etiquette among TPA children. This media is based on five main principles: Accept, Belief, Confidentiality, Empathy and Respect. The method used in this service is an interactive learning method involving 12 TPA children as subjects. Intervention is carried out through various educational activities, such as interactive games, manners simulations, discussions that focus on building positive character. The results of this service activity show that the application of the Five Basic ABC Media can provide practical understanding and ethical behavior to children, which is demonstrated through FGD activities. The conclusion from this service activity is that the Five Basic ABC Media is a fairly effective method in guiding TPA children to understand and apply etiquette in everyday life. It is hoped that this media can be a guide for TPA educators in developing character education based on Islamic values ​​in a comprehensive and enjoyable manner